Integration of soft skills in the teaching of technical courses: an exploratory study of a private university / Hairuzila Idrus - Idrus, Hairuzila (2013)
Institutions of higher education have been pressed by the industry practitioners to produce quality graduates who are ready to compete in the competitive job market locally and globally. Graduates, especially in the technical field are perceived as strong in their technical skills but are lacking in non-technical or soft skills that would enable them to use their technical skills most effectively. Thus, it is vital to integrate the soft skills in the teaching and learning process especially in the realm of engineering in order to further enhance the students’ ability in non-technical. The expected outcome would be the production of well-rounded engineering graduates with first class mentality as envisioned by the government. This empirical study attempts to craft a richer description and understanding of how soft skills are integrated into the teaching and learning of the formal curriculum focusing on technical courses at a private university in Malaysia. The study was based on both quantitative method, utilizing questionnaire survey and qualitative methods through document analysis and focus group interviews. Perspectives from both the educators and students were sought. The questionnaire survey was aimed at providing an overall pattern of the participants’ approaches and views on the integration while document analysis and focus group interviews presented the complementary details behind their reasons. Date for this study was obtained from 90 engineering lecturers, 300 final year engineering undergraduates and document from 84 engineering courses. The results of the study indicate that the most pertinent teaching approaches to be employed in integrating soft skills for technical courses are the student-centered teaching methods. The study also reveals that the lecturers place a great deal of emphasis on critical thinking and problem solving skills as well as communication skills which are crucial skills for engineers. However, the efforts taken by the lecturers in integrating soft skills were not obvious to the students. The incongruence in the lecturers and students’ perceptions was captured on the integration of critical thinking and problem solving skills (p-value = .000), leadership skills (p-value = 001), lifelong learning and information management (pvalue = .021), communication skills (p-value = 0.011), and self-awareness and ethics (p-value = .001). The findings of the study have drawn attention to the importance of paying heed to how students’ ability in soft skills are developed by the educators on their teaching since most of students’ learning time is devoted to their core courses. The findings also acknowledge the contributions of educators with industry experience to the development of students’ soft skills abilities. This research offers a novel perspective on soft skills development at higher education level. Pedagogical implications from this study focus on teaching approaches, staff and professional development, curriculum development, as well as soft skills development.